Family Visitation and Its Relationship to Parental Stress Among Jailed Fathers - Martin, Jamie S. (The prison journal, 2018)
This study explores the relationship between jail visitation with children and levels of parental stress among a sample of jailed fathers. Quantitative analyses of the self-report data reveal that jailed fathers experienced stress related to parenthood regardless of whether they had visits from their family. However, the type of stress varied, with fathers who had family visits reporting stress directly related to the visitation, while fathers who did not have visits noted more generalized parental stress. The findings provide insight into the type and quality of incarcerated fathers’ contact with their children and factors that influence the number of visits they receive. The negative impact of the lack of contact visits is also discussed.